Development of a robotic walker for individuals with cerebral palsy. (17th August 2020) - Alazem, Hana; McCormick, Anna; Nicholls, Stuart G.; Vilé, Elizabeth; Adler, Roselle; Tibi, Genevieve
Abstract: Objective: This study describes the first use of a robotic walker in youth and young adults with cerebral palsy (CP) Gross Motor Function Classification (GMFCS) IV. Methods: Semi-structured interviews were conducted before and after each robotic walker trial. Interviews were recorded, then transcribed and subjected to thematic analysis. Results: Five participants (4 male, 13–22 years of age) with quadriplegia secondary to CP were recruited. Four individuals with mixed tone quadriplegia GMFCS IV were able to independently walk with the device. One individual with significant dyskinesia was unable to utilize the device. The assessment team included two physiotherapists, an occupational therapist, a physiatrist and three engineers. Major themes related to physical and social impacts were identified. Some physical advantages include the ability to walk hands-free and promotion of physical fitness. Examples of physical barriers include limited harness design and large device size. Social advantages include increased independence and peer engagement. Finally, a social disadvantage identified was limited use on uneven terrains. Discussion: Suggestions for modifications for identified challenges and disadvantages include decreasing the size of the robotic walker, more harness designs, decreasing the force required to take an initial step, adding a joy stick for user control and creating a more versatile base that can be used on different terrains such as ice or baseball fields. Conclusion: Robotics holds great hope for individuals with CP where mobility options are limited. Physical and social advantages are evident. Recommendations for future improvement and studies of use in exercise and participation are provided. IMPLICATIONS FOR REHABILITATION: As youth and young adults with cerebral palsy age, options for mobilization can become limited with challenges in placing them in a walking device due to size and numerous other physical limitations. A robotic walker with a built-in mechanical lift is available for individuals with cerebral palsy. This study was able to gather important information and recommendations to tailor a new robotic walker prototype specifically for individuals with cerebral palsy.